Prevalence of 7 sexually transmitted organisms by multiplex real-time PCR in Fallopian tube specimens collected from Saudi women with and without ectopic pregnancy. Issue 1 (December 2015) - Ashshi, Ahmed; Batwa, Sarah; Kutbi, Seham; Malibary, Faizah; Batwa, Mohamed; Refaat, Bassem
Abstract Background Ectopic pregnancy (EP) is associated with maternal morbidity and occasionally mortality during the first trimester. A history of sexually transmitted infection (STI) and pelvic inflammatory disease have been implicated as major risk factors for EP. Our aim was to measure the prevalence ofChlamydia trachomatis (CT), Neisseria gonorrhoeae, Mycoplasma genitalium (MG), Ureaplasma parvum/urealyticum, Gardnerella vaginalis, Trichomonas vaginalis and herpes simplex virus (HSV)-1&2 in Fallopian tubes collected from EP and the results were compared with those obtained from total abdominal hysterectomy (TAH) and tubal ligation. Methods This was a prospective case–control study and tubal samples were collected from 135 Saudi women recruited from 3 centres in the Western region as follow: 84 EPs, 20 TAH and 31 tubal ligations. Multiplex TaqMan PCR was performed using an IVD CE kit for the simultaneous detection of candidate pathogens following DNA extraction. Results Infections were detected in 31.8 % of the 135 participants either as single (11.1 %) or co-infections (20.7 %) and the frequencies were significantly higher in EP (42.85 %) compared with control (13.72 %). The rates of CT (27.4 %;P  = 0.001); MG (20.2 %;P  = 0.009) and HSV-1/2 (21.4 %;P  = 0.01) were significantly higher in EP. No significant difference between the study groups was observed for the other pathogens (P  > 0.05). Binary logistic regression also showed that infection with ≥ 2 pathogens (OR 4.9; 95 % CI: 2.2 – 11.6;P  = 0.006), CT (OR 3.07; 95 % CI: 1.3 – 12.3;P  = 0.002), MG (OR 2.3; 95 % CI: 1.1 – 8.6;P  = 0.03) and HSV-1/2 (OR 1.7; 95 % CI: 0.75 – 5.7;P  = 0.004) were associated with a significantly higher risk of developing EP. Conclusions STIs are frequent in the upper genital tract of Saudi women during the reproductive age and, CT, MG and HSV-1/2 were more prevalent in EP. The observed high rates of co-infection advocate the necessity of establishing national guidelines and/or screening program utilising multiplex PCR approach for the detection of common STIs among high risk groups in the kingdom. Further studies are needed to measure the adverse reproductive outcomes associated with STIs in Saudi Arabia.